Boundary Behavior and Cesàro Means of Universal Taylor Series - Bayart, Frédéric (Revista Matemática Complutense, 2006)
We study boundary properties of universal Taylor series. We prove that if f is a universal Taylor series on the open unit disk, then there exists a residual subset G of the unit circle such that f is unbounded on all radii with endpoints in G. We also study the effect of summability methods on universal Taylor series. In particular, we show that a Taylor series is universal if and only if its Cesàro means are universal.